Розробка методу використання технологій big data та data mining в інтелектуальних системах обробки неструктурованих даних - Демченко, О. Е. (ХНУРЕ, 2020)
Many companies and organizations have difficulty trying to find out what employees or customers think about products or services, about a team or an internal organization, about working conditions or the quality of the equipment. However, if the company or organization is large enough, the process of interviewing and processing the information received becomes an extremely difficult problem. It will be best to use software systems to help solve these problems.
Keywords: big data; data mining